PSYCHOMETRIC PROPERTIES OF SELF-EFFICACY SCALE FOR ENGLISH LANGUAGE LEARNERS IN INDONESIA - Karimah, Syahadah Albaqiyatul; Yundianto, Devie; Idris, Mas Muhammad; Zulha, Hani Fatimah (University of Kuningan, 2025)
This study explores the psychometric properties of the Indonesian version of the Self-Efficacy Scale for English Language Learners (SES-ELL). With the growing importance of English proficiency in Indonesia, understanding learners’ self-efficacy beliefs—defined as confidence in their ability to perform language tasks—is crucial. The study examines the validity and reliability of the SES-ELL, utilizing a cross-sectional, quantitative approach with a sample of 165 undergraduate English language students from public and private universities. Data were collected via the adapted 32-item Questionnaire of English Self-Efficacy (QESE), measured on a 7-point scale. Results showed that the SES-ELL meets unidimensionality requirements, with Principal Component Analysis of Residuals explaining 68.6% of the variance. Reliability indicators were robust, with an Item Separation Reliability (ISR) of 0.96 and a Person Separation Reliability (PSR) of 0.97, suggesting strong differentiation among learners' self-efficacy levels. Item analysis identified four items needing revision due to fit inconsistencies. The study confirms SES-ELL as a reliable tool for measuring self-efficacy among Indonesian English learners, offering insights into their confidence across language skills. Future research should refine the scale further to ensure optimal measurement accuracy and support targeted interventions to improve learners' self-efficacy and performance in English